2016
DOI: 10.1080/03019233.2016.1209825
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the influence of changing constructive parameters of multi-strand tundish on steel flow and heat transfer

Abstract: The results of numerical simulation and industrial experiments on thermal and flow phenomena in a multi-strand tundish are presented before and after modernisation. The improvement of cast steel purity and the increase of continuous casting (CC) machine capacity was the basic aim of the research. The simplest action was to increase the height of the tundish side walls, so the working zone of tundish had a higher capacity and inside the working area a turbulence inhibitor was installed. Experimental measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…σ T = T liquid = P hydrostatic pressure (8) Where σ T = T liquid is the true stress when the temperatures is higher than the ZST (MPa); P hydrostatic pressure is the ferrostatic pressure acts on the interface between liquid and solidifying shell when the temperatures exceeding ZST (MPa). When the temperature of billet is above ZST and exceeding liquidus of steel, the flow stress can be obtained from the following eq.…”
Section: Billet Mechanical Reduction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…σ T = T liquid = P hydrostatic pressure (8) Where σ T = T liquid is the true stress when the temperatures is higher than the ZST (MPa); P hydrostatic pressure is the ferrostatic pressure acts on the interface between liquid and solidifying shell when the temperatures exceeding ZST (MPa). When the temperature of billet is above ZST and exceeding liquidus of steel, the flow stress can be obtained from the following eq.…”
Section: Billet Mechanical Reduction Modelmentioning
confidence: 99%
“…Numerical simulations method has been widely used to analyze and optimize the casting process [5][6][7][8][9]. Many researchers [10,11] have investigated the stress and strain in as-cast billets, to estimate the cracking tendency under the soft reduction process.…”
Section: Introductionmentioning
confidence: 99%
“…In the textbook [15] and the past references [16,17], the RTD curves obtained by water model and numerical simulation usually have a single flat peak, single sharp peak or double peaks [18][19][20][21]. Maybe these three types of peaks have some relations with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the increase of steel grades and the improvement of CC efficiency requirements, casting with different steel grades has become a main component of steelmaking plants. Much of the research focuses on numerical and physical analyses of the mixing process of molten steel during steady-state casting [3][4][5][6][7][8][9]. Merder et al [3] discussed the thermal and flow phenomena in a multi-strand tundish before and after modernization, found that the modernization is favourable in the aspect of transient zone during the sequence casting of different grades of steel.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research focuses on numerical and physical analyses of the mixing process of molten steel during steady-state casting [3][4][5][6][7][8][9]. Merder et al [3] discussed the thermal and flow phenomena in a multi-strand tundish before and after modernization, found that the modernization is favourable in the aspect of transient zone during the sequence casting of different grades of steel. Cwudziński et al [5] investigated liquid steel alloying process in one strand tundish, found that the species model can render the macroscopic mixing process occurring in the real metallurgical.…”
Section: Introductionmentioning
confidence: 99%